Youth climate activism in the United States - Melanie MEUNIER (E-REA)
Youths are on the front line when considering their future on a planet that is becoming less and less livable. As the frequency and intensity of extreme weather events devastate regions and impact millions, the unapologetic anti-environmentalism of the Trump administration may have been the ultimate spark that ignited mass action from the young generations. Realizing, too, that many Congress members lack the political will to effect change, an increasing number of passionate youth leaders have initiated movements to raise awareness about the urgency of acting to mitigate the worst effects of climate change. Ranging from classic street protests to electoral canvassing to litigation, their actions may be characterized in terms of “disruptive, dutiful or dangerous dissent” (O’Brien et al). They have already played a key role in electing climate-conscious, progressive candidates, put pressure on governments through lawsuits and proposed an overhaul of the American economy on greener, more equitable terms by supporting the Green New Deal. In 2019 millennials (37% of US voters) surpassed baby boomers as the largest voting demographic group and could have a significant impact on climate policy.